The in vitro inhibition of genotoxicity by plant extracts and the isolation and characterization of antimutagenic compounds from Combretum microphyllum (Combretaceae) - Eloff, Jacobus Nicolaas (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.